Characterization of newly identified bacterial biofilm degrading bacteriophage obtained from Dhaka city lake water samples - Mahdee, Munif; Abdullah, Syed Ridwan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.